Late antique pottery from an insula South of the West-Market in Miletus (Turkey) - Sossau, Veronika (Rei Cretariae Romanae Fautorum Acta, 2017)
During 1994 and 2004 W.-D. Niemeier carried out excavations in Miletus focusing on the exploration of the Bronze Age settlement and the temple of Athena. During his fieldwork, Hellenistic, Roman, and Late Antique contexts were also discovered. Among the most interesting of these late contexts is an insula situated in the South-West of the temple of Athena and South of the West-Market.